UPAYA MENINGKATKAN KEMAMPUAN KEAKSARAAN MELALUI METODE MENGGAMBAR BEBAS PADA ANAK USIA 5-6 TAHUN - Odah, Odah; Kania, Gina; Aminah, Siti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The problems found in the field indicate that the learning methods used previously were still conventional and uninteresting for children. This resulted in low ability among children to recognize letters and write simple words. This study aims to improve the literacy skills of 5–6-year-old children through free drawing methods at Cempaka III Early Childhood Education Center in Parungsari Village, West Telukjambe District, Karawang Regency. The method used in this study is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Data were obtained through observation sheets and documentation. The results showed that the average pre-action score was 13% (BSH and BSB), which increased in cycle I to 33% (BSH and BSB) and further increased in cycle II to 80% (BSH and BSB). Thus, the use of the free drawing method is effective in improving the literacy skills of 5–6-year-old children at PAUD Cempaka III. Through enjoyable drawing activities, children became more enthusiastic, creative, confident, and able to recognize and write letters and simple words better.